Комбинационный анализ переходных процессов в электроцепях с распределенными параметрами - Божко, А.Е. (Видавничий дім "Академперіодика" НАН України, 2007)
A mathematical interpretation of transient processes in electrocircuits with distributed parameters is given. A line without losses on the idling and the short-circuit mode is considered.